Talking with Your Child about School - Eboni Baugh; Donna Davis (EDIS)
“In a hurried world, keeping up with our children when we’re trying to juggle marriage, jobs, possibly multiple children, and the many other challenges life can throw at us, we can feel overwhelmed at times. However, keeping lines of communication open with your children can be critical to how they handle the challenges they face, especially when they are in school.” This 2-page Family Album Radio transcript was written by Eboni Baugh and Donna Davis, and published by the UF Department of Family, Youth and Community Sciences, March 2012.